DISRUPTIONS IN LIPID METABOLISM AND THE RESULTING DISEASES - Umurov Erkin Utkirovich (Ta'lim innovatsiyasi va integratsiyasi, 2025)
Abstract   Lipid  metabolism  plays  a  crucial  role  in  maintaining  cellular  structure  and function, energy storage, and hormone production. Disruptions in lipid metabolism can lead  to  a  variety  of  disorders,  including  dyslipidemia,  obesity,  and  cardiovascular diseases. Dyslipidemia, which includes conditions such as hypercholesterolemia and hypertriglyceridemia,  is  a  major  risk  factor  for  atherosclerosis  and other  metabolic diseases.  This  article  explores  the  mechanisms  of  lipid  metabolism,  the pathophysiology  of  metabolic  disruptions,  and  the  diseases  associated  with  these disruptions.